Epiploic Appendagitis: An Infrequent Offender in Abdominal Pain - Zacharia, George Sarin; Jacob, Anu; Vadukoot, Mathew; Ali, Muhammed (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Epiploic appendages are fat-filled outpouchings arising from the serosal surface of the colon and have uncertain physiological functions. Epiploic appendagitis is characterized by inflammation of these appendages. Primary appendagitis often results from ischemic injury, while secondary appendagitis may arise from the contiguous spread of inflammation or infection from adjacent structures. Clinical features of epiploic appendagitis include acute or subacute abdominal pain, most commonly in the lower quadrants, without significant concurrent constitutional or other gastrointestinal symptoms. Diagnosis relies on imaging modalities, with Computed Tomography (CT) being the preferred method. Management of epiploic appendagitis is mainly conservative, with analgesic and anti-inflammatory agents being the mainstay of treatment. Surgical indications are poorly defined, but laparoscopic excision of the inflamed appendage may be considered in cases of recurrent or refractory symptoms. This review article explores the anatomy, pathophysiology, clinical features, diagnosis, and management of epiploic appendages and appendagitis.